(untitled) (Colombia Medica, 1987)
A total of 6367 mosquitoes of 18 different anopheline species and 4100 were studied using the IRMA technique for the presence of Plasmodium falciparum and P. vivax sporozoites, respectively. Anopheles albimanus and A. darlingi, previously incriminated as malaria vectors, were found infected, and A. allopha and A. neomaculipalpus, two species that had never been incriminated. These results demonstrate the usefulness of this technique for entomological studies.